The Role of Istagram Social Media in Pahawang Beach Tourism Development and Creative Economy Post-Covid-19 Pandemic - Deddy Aprilani; Rosy Febriani Daud; Marini Marini; Della Monica (Indonesian Association for Public Administration (IAPA), 2022)
Tourism development as part of national development has a goal, among others, to expand business opportunities and employment opportunities. Facing the challenges during the current pandemic, efforts must be made to develop tourism and the creative economy of the coastal area of ​​Pesawaran Lampung, namely by collecting innovative ideas that become prototypes in the development of tourism and a sustainable creative economy that can be realized. The presence of social media provides significant opportunities for tourism. Therefore, social media and digital tourism are in harmony in the digital world. There are many ways to communicate through social media. Through social media, you can find, interact, and provide information with other people easily. This has an impact on drastically increasing digital tourism opportunities. The formulation of the problem of this research is how the role of Instagram media in the development of Pahawang beach tourism and the creative economy after the Covid-19 pandemic and the purpose of this research is also to find out the role of Instagram media in the development of Pahawang beach tourism and the creative economy after the Covid-19 pandemic. The method used is qualitative, namely data obtained and collected from the research process which is presented in the form of sentences. The results of qualitative research contain excerpts from the data.